The Effectiveness of Group Therapy Based on Emotional Schema Therapy (EST) on Difficulties in Emotion Regulation among Mothers having Children with Intellectual Disabilities - Keyvanlo, Safura; Nariman, Mohammad; Basharpoor, Sajjad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of group therapy based on emotional schema therapy on the difficulty of emotion regulation in mothers of mentally retarded children. Methods: The design of this experimental study was pretest-posttest with a control group. The statistical population of the study was all mothers with mentally retarded children under the age of 15 in Ardabil in the spring of 1399. For sampling, referring to the Welfare Office of Ardabil, 4 centers and schools were selected from rehabilitation centers and exceptional schools by multi-stage cluster sampling method, and 40 mothers of children with mental disabilities were selected by sampling method. Simple random sampling was selected and divided into experimental and control groups. Emotion Regulation Difficulty Scale (DERS) was used to measure the research variables. The experimental group was exposed to group emotional therapy schema for 10 sessions and the members of the control group did not receive any intervention. Data were analyzed using repeated-measures analysis of variance. Results: The results were analyzed using multivariate analysis of covariance. The results showed that the effectiveness of group therapy based on emotional schemas on the difficulty of emotion regulation (F = 115.57, P